Engineering Multiple Abiotic Stress Tolerance in Canola, Brassica napus - Lohani, Neeta; Jain, Divya; Singh, Mohan B.; Bhalla, Prem L. (Frontiers in Plant Science, 2020)
Impacts of climate change like global warming, drought, flooding, and other extreme events are posing severe challenges to global crop production. Contribution of Brassica napus towards the oilseed industry makes it an essential component of international trade and agroeconomics. Consequences from increasing occurrences of multiple abiotic stresses on this crop are leading to agroeconomic losses making it vital to endow B. napus crop with an ability to survive and maintain yield when faced with simultaneous exposure to multiple abiotic stresses. For an improved understanding of the stress sensing machinery, there is a need for analyzing regulatory pathways of multiple stress-responsive genes and other regulatory elements such as non-coding RNAs. However, our understanding of these pathways and their interactions in B. napus is far from complete. This review outlines the current knowledge of stress-responsive genes and their role in imparting multiple stress tolerance in B. napus. Analysis of network crosstalk through omics data mining is now making it possible to unravel the underlying complexity required for stress sensing and signalling in plants. Novel biotechnological approaches such as transgene-free genome editing and utilization of nanoparticles as gene delivery tools are also discussed. These can contribute to providing solutions for developing climate change resilient B. napus varieties with reduced regulatory limitations. The potential ability of synthetic biology to engineer and modify networks through fine-tuning of stress regulatory elements for plant responses to stress adaption is also highlighted.